RESEARCH OF PHYSICO-CHEMICAL TECHNOLOGY OF CERAMICS AND GLASS PRODUCTION - Niyozov Sobir Ahror o‘g‘li; Shodiyev Azimjon Ziyodullayevich; Muhitdinov Muxriddin Xudayar o‘g‘li (American Journals, 2023)
After this process, it is reduced to a size of 10-30 mm in hammer and cone crushers. Percussive grinders can also be used for this purpose. In it, the material is crushed by means of special grates installed in the body and the tukmokdar, which rotates at high speed. For the last time, the raw materials are crushed in ball mills together with the clay from the roller mill. Extraction and transportation of raw materials. Raw materials, for example, clay, are dug out from the ground in open shallow mines near the enterprise.